KONTRIBUSI PERUSAHAAN MULTINASIONAL DALAM MENGHADAPI PANDEMI COVID-19 DI INDONESIA - Muhammad Dafa Hanggariksa; Arie Kusuma Paksi (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2023)
Covid-19 is a flu disease that was first discovered in China. This epidemic spread to all corners of the world very quickly. The emergence of Covid-19 has caused various problems. To stop the spread of COVID-19, almost all countries in the world have implemented social restrictions and closed all access to and from national borders. not only health problems, as a result of the implementation of this policy, the problems caused by the Covid-19 pandemic extend to the problem of disrupting a country's economy. During the pandemic, Indonesia experienced many problems, such as the slowing pace of economic growth which led to a decline in state income, the increase in the spread of covid, health workers lacked personal protective equipment, and others. Nestle is one of the MNCs based in Indonesia. Through several programs implemented, the CSR team of PT. Nestle Indonesia has helped Indonesia face the pandemic in the economic and health fields. This study uses qualitative methods. This study explains the importance of the presence of an MNC in the guest country because it has various positive impacts on the guest country where the MNC operates. Keywords: Covid-19, CSR, MNC, NESTLE